The effects of public open spaces to double-storey housing prices In Kuala Lumpur, Malaysia - Asmawi, M. Zainora; Hj. Mohd. Noor, Norzailawati; Manzahari, Mohd Nasrul Hanis; Abdullah, Alias (International Organization Center of Academic Research (OCERINT), 2015)
This research is about a study on the effect of public open space on house price of double-storey houses in four selected neighbourhoods in Kuala Lumpur, Malaysia. It begins with an interest to study how the provision of public open space could affect the housing prices. In this regards, the double-storey terraced houses were selected as an attempt to see the degree of effect. Literatures in the global and regional settings indicate that the provision of public open space has a significant contribution to the increment of housing prices in its ambient context. In a local context, there are very few studies undertaken to investigate the relationship between the provision of public open space and house prices. Therefore, this research attempts to study the relationship between public open space and house prices in terms of its pattern and strength in the neighbourhoods of Taman Melawati, Subang Jaya, Bandar Baru Bangi and Shah Alam. This situation leads to the objectives which are to determine the elements of open spaces that influence the house prices; and to discover the relationship between open space and house prices in Kuala Lumpur. The research adopted (1) literature reviews; (2) structured close-ended questions in questionnaire survey; and (3) site observation for data collection, surveyed a total of 200 double-storey terraced houses in Bandar Baru Bangi, Taman Melawati, Subang Jaya and Shah Alam. The results of Cronbach‟s alpha value for green areas and its independent variables were 0.895 and considered acceptable, allowing the research to retain all variables for the analysis. The finding shows that the respondents preferred cleanliness as the most important element of open space; followed by regular maintenance, facilities provided for the users and the strategic location of open space; these reflecting the elements of the management aspect rather than the planning aspect of open space. In addition, the finding also suggests that the relationship between the provision of public open space and house prices does establish a positive pattern. However, it is not considered as a strong association. To conclude, this research has achieved its objectives, proven that there is a relationship between the provision of public open space and house price in the context of the Malaysian housing market.